SPILANTHES ACMELLA AND ITS MEDICINAL USES – A REVIEW - Purushothaman, Yasodha; Gunaseelan, Silambarasan; Vijayakumar, Sudarshana Deepa (Asian Journal of Pharmaceutical and Clinical Research, 2018)
ABSTRACT In common plant life has been recognized to alleviate various diseases. Spilanthes acmella- a vital native medicinal plant, is also found in sub continent of America. A range of abstracts and active metabolites from different parts of this plant is found to contain valuable pharmacological activities. Traditionally recognized as tooth ache plant, it is known to suppress the ailment allied with tooth aches and is found to stimulate saliva secretion. On Survey of literatures it has been projected that, it has numerous drug related actions, which comprises of antimicrobial, antipyretic, local anaesthetic, bioinsecticide against insects of agricultural importance, antioxidant, analgesic, antimicrobial, vasorelaxant, anti-human immune deficit virus, tooth ache relief and anti-inflammatory effects. Based on the traditional claims against a range of diseases, researchers have classified and estimated plants for their bioactive compounds. However researchers found it to be a difficult task for the extraction of bioactive constituents from these plants. Therefore the scientific information about Spilanthes acmella could be obtained from this current review. Â Â